El debate sobre el peronismo y la democracia - Fair , Hernán (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The work analyzes the ideological debate on the phenomenon of peronism and the question of democracy. It affirms that there are two main perspectives that compete among themselves: democracy as a political regime or institutional democracy and democracy as inclusion of unsatisfied social demands or social democracy. From a temporal analysis focused on the Argentine case, tries to give account the characteristics and differences between both approaches.